Car braking effectiveness after adaptation for drivers with motor dysfunctions - Sowiński Adam (De Gruyter, 2021)
This article presents the results of measurements of the braking efficiency of vehicles adapted to be operated by drivers with motor dysfunctions. In such cars, the braking system is extended with an adaptive device that allows braking with the upper limb. This device applies pressure to the original brake in the car. The braking force and thus its efficiency depend on the mechanical ratio in the adapting device. In addition, braking performance depends on the sensitivity of the car’s original braking system and the maximum force that a disabled person can exert on the handbrake lever. Such a person may have limited power in the upper limbs. The force exerted by the driver can also be influenced by the position of the driver’s seat in relation to the handbrake lever. This article describes the research aimed at understanding the influence of the above-mentioned factors on the car braking performance. As a part of the analysis of the test results, a mathematical function was proposed that allows a parametric description of the braking efficiency index on the basis of data on the braking system, adaptation device, driver’s motor limitations, and the position of the driver’s seat. The information presented in this article can be used for the preliminary selection of adaptive devices to the needs of a given driver with a disability and to the vehicle construction.